Potential advantages of applying a centralized chilled water system to high-density urban areas in China - Kang, Di (Kansas State University, 2017)
This paper discusses the advantages of applying a utility centralized chilled water system as the district cooling choice for facilities in the high-density urban areas of China and how it will influence China’s development in the next decades. Presently, the Chinese government is trying to contribute to the world’s energy-saving goals as well as determine its sustainable development framework. As air pollution has become one of the main problems in China, indoor air quality (IAQ) is likely to gain priority as a building design consideration in the future. Consistent with this fact, this paper proposes an optimum HVAC system for cooling purposes to the Chinese government. Compared to unitary HVAC systems, the centralized HVAC system has significant advantages in system efficiency, energy reduction and cost savings and can, therefore, be a better choice. Furthermore, the paper will focus on the centralized chilled water system and demonstrate why they better match the development model in China. The application of the system in high-density urban areas will also be discussed. Due to a lack of understanding that the energy consumption of unitary systems, the first comparison presented is between unitary HVAC systems and centralized HVAC systems in individual buildings. The comparison presented will focus on the energy-saving benefits of the centralized HVAC system in individual buildings and its contribution to sustainable development. Consequently, prescribing a centralized chilled water system as a utility district cooling system and applying a centralized chilled water system to each individual building in the highdensity urban areas will be compared. Cost savings, including initial cost and life cycle cost, are the metrics used in this comparison. Additionally, energy consumption and system reliability will be explored in determining which model will be more appropriate for China's development. The paper concludes that the centralized chilled water system should become the mainstream in the high-density urban area in China. Several recommendations are also made to the Chinese government on setting up utility centralized chilled water systems.
Keywords: China; Chilled water systems; CoolingUtility district cooling system